Use of versapoint to refashion the cervical canal to overcome unusually difficult embryo transfers and improve in-vitro fertilization-embryo transfer outcome: A case series - Nalini Mahajan; Ila Gupta (Wolters Kluwer Medknow Publications, 2011)
Background : Smooth atraumatic embryo transfer is paramount for the success of in-vitro fertilization (IVF). In difficult cases, cervical canal manipulation may be required. Aim : To see if surgical correction of the cervical canal or cervical canal refashioning could improve ease of embryo transfer. Setting : Private infertility and IVF hospital. Design : Prospective study. Materials and Methods : Patients: 11 women with failed 1-3 IVF cycles with history of extremely difficult embryo transfers (ETs) despite undergoing cervical dilatation in the cycle prior to IVF. Interventions : Operative hysteroscopy using Versapoint for refashioning of the cervical canal. Main Outcome Measures : Ease of ET in the subsequent IVF cycle. Secondary outcome measure was to assess reproductive outcome. Results : Easy and atraumatic ET in the IVF cycle after procedure in 100% patients. PR was 46.5%. Conclusions : Use of Versapoint for refashioning the cervical canal can improve the quality of ET and PR.